PEMBANGUNAN IDENTITAS MELALUI SAPAAN KEKERABATAN DI MASYARAKAT PINGGIRAN ANTARA BANDUNG DAN JATINANGOR - Lina Meilinawati Rahayu (Balai Bahasa Kalimatan Selatan, 2019)
This paper aims to analyse and reveals how the construction of new identities in urban communities, on the outskirts of Bandung is displayed through kinship address terms. The theory used is Jenkins (2008) identity theory using Baurdrillard's (1983) perspective in seeing the relationship between reality, symbols, and society. Baudrillard explains that the typical character of today’s community is a simulation community. Furthermore, they are being explained as community who lives with crisscross code and signs. Hereafter, language, especially the address terms of kinship will be placed as a cultural discourse. The method used to see these cultural phenomena is literature and field studies. Field studies focused on distributing questionnaires to informants. Field data is then processed based on theories that have been obtained through literature study. The results of this study indicate that there is a shift in the function of kinship address terms from use-value to sign-value or symbol-value. Signs and values which consist of status, prestige, style expression, lifestyle, can be the main motives for the abovementioned changes kinship address terms.